Effect of nozzles blocking on the circulation flow rate in RH vacuum equipment - LI Yi-hong; SHEN Xiao-wei; TANG De-chi; HUANG Qing-xue (工程科学学报)
Based on the similarity principle, a water model with a scale of 1:4 of a 300 t RH unit was established to study the effect of different modes of nozzles blocking on the RH circulation flow rate. Results show that the deviation of gas volume is the main factor influencing the circulation flow rate in the case of nozzles blocking. In the situation of symmetrical blocking, the circulation flow rate is minimum when the angle of the attachment of the blocking position and circulation direction is 0o, on the contrary, the circula-tion flow rate is maximum when the angle is 90o. In the situation of concentrated blocking, with the increase of the number of blocked nozzles, the mechanism of bubble pump action shifts from the annular bubble pump mechanism to the cluster bubble pump mechanism and the circulation flow rate is increased.